The Peterborough Exemplar: a protocol to evaluate the impact and implementation of a new patient-centred, system-wide community mental healthcare model in England - Lida Efstathopoulou; Grace Jagger; Jules Mackenzie; Kathryn Faulkner; Trish Barker-Barrett; Rory Cameron; Adam P. Wagner; Jesus Perez (Health Research Policy and Systems, 2022)
Abstract Background Community mental healthcare has significantly grown since de-institutionalization. Despite progress, service fragmentation and gaps in service provision remain key barriers to effective community care in England. Recent mental healthcare policies highlighted the need to transform service provision by developing patient-centred, joined-up community mental healthcare. In response to policy guidance, a system-wide community mental healthcare model was developed in Peterborough (England). The “Peterborough Exemplar” is based on two main pillars: (1) the creation of knowledge exchange pathways to strengthen interorganizational relationships, and (2) the development of new, accessible community services addressing existing service gaps. This paper presents the protocol developed to evaluate the Peterborough Exemplar. Methods A quasi-experimental design with an intervention group and a nonequivalent comparator group has been developed to compare service provision provided in Peterborough pre- and post-intervention with services provided in Fenland, a neighbouring area where service users access usual care. Two evaluation methods will be employed to compare service provision between the two groups: (1) outcome measures completed by service users and carers will be analysed to assess quality of life and service satisfaction, and (2) service activity data will be analysed to assess service usage. In addition, qualitative interviews will be conducted with staff members of participating organizations to explore the implementation of the Exemplar in Peterborough and evaluate knowledge exchange processes among local service providers. A matched control approach will be used to compare outcome measures between the two areas. Descriptive and inferential statistics, including chi-square tests, will be used to analyse service activity data and examine differences between the two areas. A thematic analysis will be adopted to analyse qualitative data. Discussion Outcomes of the evaluation will contribute to understanding the contribution of the Peterborough Exemplar on mental health service provision locally. Evaluation findings and intermediate reporting will be shared with organizations involved in the implementation of the Peterborough Exemplar and with local decision-makers to inform the Exemplar delivery. As the Peterborough Exemplar is an Early Implementer (EI) site funded by NHS England, findings will be shared with policy-makers to inform national policy on community mental healthcare and integrated care.